85‐2: Invited Paper: Fourth Gen Optics ‐ Planar Optics Revolutionized by LCD Technology. Issue 1 (25th September 2020) - Tabiryan, Nelson; Roberts, David; Kimball, Brian; Steeves, Diane; Bunning, Timothy J.
Abstract : We will review the state‐of‐the‐art of the Fourth Generation Optics ‐ a planar optics rooted in LCD technology, ‐ and the advance it has enabled in display, AR/VR, imaging, and other critical modern technologies beyond displays. The review will lead to the conclusion that the technology is mature for many applications offering the most versatile and efficient techniques for controlling light with truly flat, thin film, achromatic, and high quality optical systems produced at low manufacturing cost inherent to LCDs.